Reinforcing Film

The reinforcing film with a base and adhesive layer, along with a surface protection film, addresses the issue of retardation changes in harsh environments, maintaining stability and inspection reliability.

JP7607584B2Active Publication Date: 2024-12-27NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021561157
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-07-27
Publication Date
2024-12-27
Estimated Expiration
2040-07-27

AI Technical Summary

Technical Problem

Reinforcing films used on optical and electronic components suffer from changes in retardation when stored in harsh environments, leading to rainbow unevenness and poor inspection performance.

Method used

A reinforcing film with a base layer and adhesive layer, having specific in-plane retardation, haze change rate, and total light transmittance values, along with a surface protection film, to maintain stability and testability under harsh conditions.

Benefits of technology

The film suppresses changes in retardation and maintains high light transmittance, ensuring reliable inspection performance even after prolonged storage in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607584000003
    Figure 0007607584000003
  • Figure 0007607584000004
    Figure 0007607584000004
  • Figure 0007607584000005
    Figure 0007607584000005
Patent Text Reader

Abstract

A reinforcing film which can be stuck to an optical member or electronic member, and which suppresses a change in phase difference and does not reduce inspectability when said optical member or electronic member is inspected through the reinforcing film. Also provided is a reinforcing film-equipped optical member or reinforcing film-equipped electronic member which is equipped with such a reinforcing film. Further provided are a surface protection film-equipped reinforcing film obtained by providing such a reinforcing film with a surface protection film, and a method for using such a surface protection film-equipped reinforcing film. A reinforcing film according to an embodiment of the present invention which contains a substrate layer A1 and an adhesive layer A2, wherein the absolute value of the rate of change in the in-plane phase difference (R0) at a wavelength of 590nm after storing the reinforcing film in a 60°C, 90%RH environment for one week is 20.0% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reinforcing film. [Background technology]

[0002] In order to impart rigidity and impact resistance to optical and electronic components such as organic EL panels, LCD panels, and touch panels, a reinforcing film may be attached in advance to the exposed surfaces of the optical and electronic components to reinforce them (Patent Document 1).

[0003] Furthermore, in order to prevent the surface from being scratched during processing, assembly, inspection, transportation, etc., the reinforcing film may be used with a surface protection film attached in advance to the exposed surface of the reinforcing film. When surface protection is no longer required, such a surface protection film is peeled off from the reinforcing film (Patent Document 2).

[0004] Such a reinforcing film may be attached to an optical member or an electronic member, and the optical member or the electronic member may be inspected through the reinforcing film.

[0005] However, when a reinforcing film is attached to an optical or electronic component and stored in a harsh environment for a long period of time, the phase difference of the reinforcing film may change, causing rainbow unevenness and other problems that reduce inspectability.

[0006] As described above, in a reinforcing film that is attached to an optical component or electronic component so that the optical component or electronic component can be inspected through the reinforcing film, it is important to improve the reinforcing film, i.e., to suppress changes in the phase difference of the reinforcing film when the reinforcing film is attached to an optical component or electronic component and stored for long periods in harsh environments. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6366199 [Patent Document 2] JP 2016-17109 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a reinforcing film that can be attached to an optical component or an electronic component, and that suppresses changes in phase difference and does not reduce inspectability when the optical component or electronic component is inspected through the reinforcing film. It also aims to provide an optical component with a reinforcing film or an electronic component with a reinforcing film that includes such a reinforcing film. It also aims to provide a reinforcing film with a surface protective film in which such a reinforcing film is provided with a surface protective film, and to provide a method for using such a reinforcing film with a surface protective film. [Means for solving the problem]

[0009] The reinforcing film according to an embodiment of the present invention is A reinforcing film comprising a base layer A1 and a pressure-sensitive adhesive layer A2, After storing the reinforcing film in an environment of 60° C. and 90% RH for one week, the absolute value of the rate of change in in-plane retardation (R0) at a wavelength of 590 nm is 20.0% or less.

[0010] In one embodiment, the reinforcing film has a rate of change in haze of 10.0% or less after storage for one week in an environment of 60° C. and 90% RH.

[0011] In one embodiment, the reinforcing film has a total light transmittance of 80% or more.

[0012] In one embodiment, the reinforcing film according to the embodiment of the present invention has an adhesive strength to a PET film of 0.30 N / 25 mm or more at a peel angle of 180 degrees and a peel speed of 300 mm / min after the above-mentioned adhesive layer A2 is attached to a PET film and left at 23°C for 30 minutes.

[0013] In one embodiment, the reinforcing film according to the embodiment of the present invention is attached to an adherend that is an optical member or an electronic member.

[0014] The optical member with a reinforcing film or the electronic member with a reinforcing film according to the embodiment of the present invention includes the reinforcing film according to the embodiment of the present invention.

[0015] The reinforcing film with a surface protective film according to the embodiment of the present invention includes a surface protective film on the above-mentioned base layer A1 side of the reinforcing film according to the embodiment of the present invention.

[0016] A method of using the reinforcing film with a surface protective film of the present invention involves exposing the adhesive layer A2 provided on the reinforcing film with a surface protective film according to an embodiment of the present invention, attaching the adhesive layer A2 to an adherend, and then peeling off the surface protective film. Effect of the Invention

[0017] According to the present invention, it is possible to provide a reinforcing film that can be attached to an optical component or an electronic component, and that suppresses changes in phase difference and does not reduce inspectability when the optical component or the electronic component is inspected through the reinforcing film. It is also possible to provide an optical component with a reinforcing film or an electronic component with a reinforcing film that includes such a reinforcing film. It is also possible to provide a reinforcing film with a surface protective film in which such a reinforcing film is provided with a surface protective film, and a method for using such a reinforcing film with a surface protective film. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of a reinforcing film according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of another embodiment of the reinforcing film in the embodiment of the present invention. [Diagram 3]FIG. 1 is a schematic cross-sectional view of one embodiment of a surface protection film. [Figure 4] FIG. 2 is a schematic cross-sectional view of another embodiment of a surface protection film. [Diagram 5] 1 is a schematic cross-sectional view of one embodiment of a surface protective film-attached reinforcing film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] When the term "mass" appears in this specification, it may be read as "weight", which is the commonly used unit of weight, and conversely, when the term "weight" appears in this specification, it may be read as "mass", which is the commonly used SI unit of weight.

[0020] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein".

[0021] ≪1. Reinforcing film≫ The reinforcing film of the present invention includes a base layer A1 and a pressure-sensitive adhesive layer A2. The reinforcing film of the present invention may have any other appropriate layer as long as it has the base layer A1 and the pressure-sensitive adhesive layer A2, as long as the effect of the present invention is not impaired. Typically, the reinforcing film of the present invention is composed of the base layer A1 and the pressure-sensitive adhesive layer A2.

[0022] A release sheet, which will be described later, may be provided on the surface of the pressure-sensitive adhesive layer A2 for protection.

[0023] A functional layer A3, which will be described later, may be provided on the surface of the base material layer A1 in order to impart various functions.

[0024] The thickness of the reinforcing film may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 5 μm to 800 μm, more preferably 10 μm to 650 μm, further preferably 20 μm to 550 μm, and particularly preferably 25 μm to 450 μm.

[0025] One embodiment of the reinforcing film, as shown in FIG. 1, is composed of a base layer A1 (10) and a pressure-sensitive adhesive layer A2 (20).

[0026] The reinforcing film of the present invention has an absolute value of the rate of change of the in-plane retardation (R0) at a wavelength of 590 nm after storing the reinforcing film in an environment of 60° C. and 90% RH for one week, which is 20.0% or less, preferably 15.0% or less, more preferably 12.0% or less, even more preferably 10.0% or less, and particularly preferably 9.5% or less. If the absolute value of the rate of change of the in-plane retardation (R0) at a wavelength of 590 nm is within the above range, a reinforcing film can be provided that does not deteriorate in inspectability when optical components or electronic components are inspected through the reinforcing film.

[0027] The reinforcing film of the present invention has a haze change rate after storage for one week in an environment of 60° C. and 90% RH of preferably 10.0% or less, more preferably 7.0% or less, even more preferably 6.0% or less, even more preferably 5.0% or less, particularly preferably 4.0% or less, and most preferably 3.5% or less. If the haze change rate is within the above range, a reinforcing film can be provided that does not deteriorate in inspectability when optical members or electronic members are inspected through the reinforcing film.

[0028] The total light transmittance of the reinforcing film of the present invention is preferably 80% or more, more preferably 83% or more, even more preferably 85% or more, and particularly preferably 88% or more. If the total light transmittance of the reinforcing film is within the above range, a reinforcing film can be provided that does not deteriorate the inspectability when an optical component or an electronic component is inspected through the reinforcing film.

[0029] <1-1. Base material layer A1> As the substrate layer A1, a substrate made of any suitable material may be used depending on the purpose, as long as the effect of the present invention is not impaired. Examples of such materials include resin sheets, nonwoven fabrics, paper, metal foils, woven fabrics, rubber sheets, foam sheets, and laminates thereof (particularly laminates containing resin sheets).

[0030] Examples of resins that may be used to form the resin sheet include acrylic resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, polyether ether ketone (PEEK), and cyclic olefin polymers.

[0031] Examples of nonwoven fabrics include nonwoven fabrics made of heat-resistant natural fibers such as nonwoven fabrics containing Manila hemp; and synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabrics, polyethylene resin nonwoven fabrics, and ester resin nonwoven fabrics.

[0032] The base material layer A1 may be a single layer or may be two or more layers.

[0033] The thickness of the base layer A1 may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 4 μm to 500 μm, more preferably 10 μm to 400 μm, further preferably 15 μm to 350 μm, and particularly preferably 20 μm to 300 μm.

[0034] The total light transmittance of the base material layer A1 is preferably 90% or more, more preferably 91% or more, even more preferably 92% or more, and particularly preferably 93% or more. If the total light transmittance of the base material layer A1 is within the above range, a reinforcing film can be provided that does not deteriorate the inspectability when an optical component or an electronic component is inspected through the reinforcing film.

[0035] The base layer A1 may contain an antistatic agent. For example, a resin sheet in which an antistatic agent is kneaded may be used as the base layer A1 containing an antistatic agent. Such a resin sheet may be formed from a composition for forming the base layer A1 that contains a resin and an antistatic agent.

[0036] The base layer A1 itself may act as an antistatic agent. For example, when a metal foil is used as the material of the base layer A1, the base layer A1 itself may act as an antistatic agent.

[0037] The substrate layer A1 may be subjected to a surface treatment, such as a corona treatment, a plasma treatment, a chromic acid treatment, an ozone exposure, a flame exposure, a high-voltage shock exposure, an ionizing radiation treatment, or a coating treatment with a primer.

[0038] Examples of organic coating materials include materials described in Plastic Hard Coat Materials II (CMC Publishing, (2004)). As such organic coating materials, preferably, urethane-based polymers are used, and more preferably, polyacrylic urethane, polyester urethane, or precursors thereof are used. This is because they are easy to apply to the substrate layer A1, and a wide variety of them can be selected industrially and are inexpensively available. Examples of such urethane-based polymers include polymers made of a reaction mixture of an isocyanate monomer and an alcoholic hydroxyl group-containing monomer (e.g., a hydroxyl group-containing acrylic compound or a hydroxyl group-containing ester compound). The organic coating material may contain, as an optional additive, a chain extender such as polyamine, an antiaging agent, an oxidation stabilizer, and the like.

[0039] The substrate layer A1 may contain any other appropriate additives depending on the purpose, as long as the effects of the present invention are not impaired.

[0040] <1-2. Adhesive layer A2> The thickness of the pressure-sensitive adhesive layer A2 may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 1 μm to 300 μm, more preferably 2 μm to 250 μm, further preferably 4 μm to 200 μm, and particularly preferably 5 μm to 150 μm.

[0041] The pressure-sensitive adhesive layer A2 may consist of only one layer, or may consist of two or more layers.

[0042] The pressure-sensitive adhesive layer A2 may contain a conductive component. The conductive component may be of only one type, or of two or more types.

[0043] The adhesive strength to the PET film after the pressure-sensitive adhesive layer A2 is attached to a PET film and left at 23°C for 30 minutes at a peel angle of 180 degrees and a peel speed of 300 mm / min is preferably 0.30 N / 25 mm or more, more preferably 1 N / 25 mm to 40 N / 25 mm, even more preferably 5 N / 25 mm to 35 N / 25 mm, and particularly preferably 10 N / 25 mm to 30 N / 25 mm.

[0044] The adhesive strength to the PET film after the pressure-sensitive adhesive layer A2 is attached to a PET film and left at 60°C for 60 minutes at a peel angle of 180 degrees and a peel speed of 300 mm / min is preferably 10 N / 25 mm or more, more preferably 10 N / 25 mm to 40 N / 25 mm, even more preferably 15 N / 25 mm to 35 N / 25 mm, and particularly preferably 20 N / 25 mm to 30 N / 25 mm.

[0045] The adhesive layer A2 is formed from an adhesive composition a2. The adhesive layer A2 can be formed by any appropriate method as long as the adhesive composition a2 can be formed into a layer. For example, the adhesive layer A2 can be formed by applying the adhesive composition a2 onto any appropriate substrate, and optionally heating, irradiating with active energy rays (such as ultraviolet rays), drying, and optionally curing the composition to form an adhesive layer on the substrate. Examples of such application methods include methods using a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roll brush coater.

[0046] The pressure-sensitive adhesive composition a2 preferably contains a polymer component, since this can further exert the effects of the present invention.

[0047] The polymer component is preferably at least one selected from the group consisting of acrylic polymers, urethane polymers, and silicone polymers, with the acrylic polymer being described below as a representative example.

[0048] The acrylic polymer may be referred to as a so-called base polymer in the field of acrylic pressure sensitive adhesives. The acrylic polymer may be one type only, or two or more types may be used.

[0049] The content of the acrylic polymer in the pressure-sensitive adhesive composition a2, calculated as solid content, is preferably 60 wt% to 99.999 wt%, more preferably 65 wt% to 99.99 wt%, even more preferably 70 wt% to 99.9 wt%, particularly preferably 75 wt% to 99.9 wt%, and most preferably 80 wt% to 99.9 wt%.

[0050] As the acrylic polymer, any appropriate acrylic polymer can be adopted as long as it does not impair the effects of the present invention.

[0051] The weight average molecular weight of the acrylic polymer is preferably 300,000 to 2.5 million, more preferably 350,000 to 2 million, even more preferably 400,000 to 1.8 million, and particularly preferably 500,000 to 1.5 million, in order to further exert the effects of the present invention.

[0052] As the acrylic polymer, from the viewpoint of being able to more effectively exhibit the effects of the present invention, it is preferable to use an acrylic polymer formed by polymerization from a composition (A) containing: (component a) a (meth)acrylic acid alkyl ester in which the alkyl group in the alkyl ester moiety has 4 to 12 carbon atoms; and (component b) at least one selected from the group consisting of a (meth)acrylic acid ester having an OH group and (meth)acrylic acid.

[0053] Each of (a component) and (b component) may independently be one type or two or more types.

[0054] Examples of (meth)acrylic acid alkyl esters (component a) having an alkyl group of 4 to 12 carbon atoms in the alkyl ester moiety include n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, in terms of being able to further exert the effects of the present invention, preferred are n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, and more preferred are n-butyl acrylate and 2-ethylhexyl acrylate.

[0055] Examples of the at least one (b) selected from the group consisting of (meth)acrylic acid esters having an OH group and (meth)acrylic acid include (meth)acrylic acid esters having an OH group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, and (meth)acrylic acid. Among these, in terms of being able to more effectively exert the effects of the present invention, preferred are hydroxyethyl (meth)acrylate and (meth)acrylic acid, and more preferred are hydroxyethyl acrylate and acrylic acid.

[0056] The composition (A) may contain a copolymerizable monomer other than the components (a) and (b). The copolymerizable monomer may be one type only, or two or more types. Examples of such copolymerizable monomers include (meth)acrylic acid alkyl esters in which the alkyl group in the alkyl ester moiety has 1 to 3 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate; carboxyl group-containing monomers (excluding (meth)acrylic acid) such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and acid anhydrides thereof (for example, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride); amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; and epoxy group-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate. Monomers containing cyano groups, such as acrylonitrile and methacrylonitrile; heterocyclic vinyl monomers, such as N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, vinylpyridine, vinylpyrimidine, and vinyloxazole; sulfonic acid group-containing monomers, such as sodium vinyl sulfonate; phosphoric acid group-containing monomers, such as 2-hydroxyethyl acryloyl phosphate; imide group-containing monomers, such as cyclohexylmaleimide and isopropylmaleimide; isocyanate group-containing monomers, such as 2-methacryloyloxyethyl isocyanate; (meth)acrylic acid esters having alicyclic hydrocarbon groups, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid esters having aromatic hydrocarbon groups, such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate;Examples of the vinyl esters include vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyl toluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.

[0057] As the copolymerizable monomer, a polyfunctional monomer may also be used. The polyfunctional monomer refers to a monomer having two or more ethylenically unsaturated groups in one molecule. As the ethylenically unsaturated group, any appropriate ethylenically unsaturated group may be used within a range that does not impair the effects of the present invention. Examples of such ethylenically unsaturated groups include radically polymerizable functional groups such as vinyl groups, propenyl groups, isopropenyl groups, vinyl ether groups (vinyloxy groups), and allyl ether groups (allyloxy groups). Examples of the polyfunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, etc. Such polyfunctional monomers may be used alone or in combination of two or more kinds.

[0058] As the copolymerizable monomer, (meth)acrylic acid alkoxyalkyl esters may also be used. Examples of (meth)acrylic acid alkoxyalkyl esters include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The (meth)acrylic acid alkoxyalkyl esters may be one type or two or more types.

[0059] The content of the (meth)acrylic acid alkyl ester (component a) in which the alkyl group in the alkyl ester moiety has 4 to 12 carbon atoms is, in order to more effectively exert the effects of the present invention, preferably 30% by weight or more, more preferably 35% by weight to 99% by weight, even more preferably 40% by weight to 98% by weight, and particularly preferably 50% by weight to 96% by weight, relative to the total amount (100% by weight) of the monomer components constituting the acrylic polymer.

[0060] The content of at least one type (component b) selected from the group consisting of (meth)acrylic acid esters having an OH group and (meth)acrylic acid is preferably 1 wt % or more, more preferably 1 wt % to 30 wt %, even more preferably 2 wt % to 20 wt %, and particularly preferably 3 wt % to 15 wt %, relative to the total amount (100 wt %) of the monomer components constituting the acrylic polymer, in order to further exert the effects of the present invention.

[0061] The composition (A) may contain any appropriate other components as long as the effects of the present invention are not impaired. Examples of such other components include a polymerization initiator, a chain transfer agent, a solvent, etc. The content of these other components may be any appropriate content as long as the effects of the present invention are not impaired.

[0062] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc., depending on the type of polymerization reaction. The polymerization initiator may be one type only, or two or more types.

[0063] The thermal polymerization initiator may be preferably used when obtaining an acrylic polymer by solution polymerization. Examples of such thermal polymerization initiators include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), and redox polymerization initiators. Among these thermal polymerization initiators, the azo polymerization initiators disclosed in JP-A-2002-69411 are particularly preferred. Such azo polymerization initiators are preferred in that decomposition products of the polymerization initiator are unlikely to remain in the acrylic polymer as a portion that causes the generation of gas generated by heating (outgassing). Examples of the azo polymerization initiator include 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionate) dimethyl, and 4,4'-azobis-4-cyanovaleric acid.

[0064] The photopolymerization initiator can be preferably used when obtaining an acrylic polymer by active energy ray polymerization. Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.

[0065] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethan-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin-based photopolymerization initiators include benzoin. Examples of benzyl-based photopolymerization initiators include benzyl. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. Examples of ketal-based photopolymerization initiators include benzyl dimethyl ketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0066] The adhesive composition a2 may contain a crosslinking agent. By using the crosslinking agent, the cohesive strength of the acrylic adhesive can be improved, and the effects of the present invention can be more effectively exhibited. The crosslinking agent may be one type only, or two or more types.

[0067] Examples of the crosslinking agent include polyfunctional isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, at least one type (component c) selected from the group consisting of polyfunctional isocyanate-based crosslinking agents and epoxy-based crosslinking agents is preferred in terms of further exerting the effects of the present invention.

[0068] Examples of polyfunctional isocyanate crosslinking agents include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of polyfunctional isocyanate crosslinking agents include commercially available products such as trimethylolpropane / tolylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), product name "Coronate HX" (Nippon Polyurethane Industry Co., Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., product name "Takenate 110N").

[0069] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, and ethylene glycol diglycidyl ether. Examples of the epoxy crosslinking agent include diglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of the epoxy crosslinking agent include commercially available products such as "Tetrad C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0070] The content of the crosslinking agent in the pressure-sensitive adhesive composition a2 may be any appropriate content within the range that does not impair the effects of the present invention. For example, such a content is preferably 0.005 to 20 parts by weight, more preferably 0.05 to 18 parts by weight, even more preferably 0.01 to 15 parts by weight, and particularly preferably 0.1 to 10 parts by weight, relative to the solid content (100 parts by weight) of the acrylic polymer, in terms of being able to further exhibit the effects of the present invention.

[0071] The adhesive composition a2 may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of such other components include polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifier resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antiaging agents, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foil-like materials, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.

[0072] The pressure-sensitive adhesive composition a2 preferably does not contain an oligomer (X) obtained from a monomer composition containing an acrylic monomer having a three or more ring structure as a main component. In this case, the content ratio of the acrylic monomer having a three or more ring structure relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (X) is preferably 50 parts by weight or more, more preferably 60 parts by weight to 99 parts by weight, even more preferably 70 parts by weight to 98 parts by weight, and particularly preferably 80 parts by weight to 96 parts by weight. Since the pressure-sensitive adhesive composition a2 does not contain an oligomer (X) obtained from a monomer composition containing an acrylic monomer having a three or more ring structure as a main component, a reinforcing film can be provided that does not deteriorate in inspectability when optical components or electronic components are inspected through the reinforcing film.

[0073] Examples of acrylic monomers having a three or more ring cyclic structure include dicyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentanyl methacrylate, dicyclopentanyloxyethyl methacrylate, dicyclopentanyloxyethyl acrylate, tricyclopentanyl methacrylate, tricyclopentanyl acrylate, 1-adamantyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-methyl-2-adamantyl acrylate, 2-ethyl-2-adamantyl methacrylate, and 2-ethyl-2-adamantyl acrylate.

[0074] The acrylic monomer having a tricyclic or higher ring structure may be of only one type, or of two or more types.

[0075] The monomer composition used to obtain the oligomer (X) may contain other monomers in addition to the acrylic monomer having a tricyclic or higher cyclic structure. Such other monomers may be of only one type or of two or more types.

[0076] Examples of other monomers include (meth)acrylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and isodecyl (meth)acrylate. alkyl esters; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; vinyl ester monomers such as vinyl acetate and vinyl propionate; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylate monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; olefin monomers such as ethylene, propylene, isoprene and butadiene; and vinyl ether monomers such as vinyl ether.

[0077] Other monomers also include polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, and hexyl di(meth)acrylate.

[0078] Other monomers also include nitrogen atom-containing monomers (for example, aminoalkyl (meth)acrylate monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; (N-substituted) amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hydroxy(meth)acrylamide; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; and isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate).

[0079] The pressure-sensitive adhesive composition a2 may contain an oligomer (Y) other than the oligomer (X). However, in order to more effectively exert the effects of the present invention, it is preferable that the content of the oligomer (Y) is small.

[0080] In order to further exert the effects of the present invention, the content of the oligomer (Y) in the pressure-sensitive adhesive composition a2 is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, even more preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less, relative to 100 parts by weight of the acrylic polymer contained in the pressure-sensitive adhesive composition a2.

[0081] The oligomer (Y) is preferably an oligomer obtained from a monomer composition containing an acrylic monomer having a two or less ring cyclic structure as a main component and containing a carboxyl group-containing monomer in an amount of 1 to 10 parts by weight per 100 parts by weight of the total amount of the monomer components.

[0082] The bicyclic or less cyclic structure may be either an aromatic ring or a non-aromatic ring, but is preferably a non-aromatic ring. Examples of the aromatic ring include aromatic hydrocarbon rings (e.g., benzene rings and condensed carbon rings such as naphthalene) and various aromatic heterocycles. Examples of the non-aromatic ring include non-aromatic alicyclic rings (cycloalkane rings such as cyclopentane ring, cyclohexane ring, cycloheptane ring, and cyclooctane ring; cycloalkene rings such as cyclohexene ring), and non-aromatic bridged rings (bicyclic hydrocarbon rings such as pinane, pinene, bornane, norbornane, and norbornene).

[0083] Examples of acrylic monomers having a two or less ring cyclic structure include ethylenically unsaturated monomers having a cyclic structure in the molecule, such as (meth)acrylic acid cycloalkyl esters such as cyclohexyl (meth)acrylate, (meth)acrylic acid aryl esters such as phenyl (meth)acrylate, (meth)acrylic acid aryloxyalkyl esters such as phenoxyethyl (meth)acrylate, (meth)acrylic acid arylalkyl esters such as benzyl (meth)acrylate, and styrene-based monomers such as styrene and α-methylstyrene.

[0084] Examples of acrylic monomers having a cyclic structure with two or less rings include preferably (meth)acrylic acid esters having a non-aromatic ring, such as cyclohexyl methacrylate and isobornyl (meth)acrylate, and from the viewpoint of transparency, more preferably cyclohexyl methacrylate.

[0085] The acrylic monomer having a two or less ring cyclic structure may be of only one type, or of two or more types.

[0086] The content of the acrylic monomer having a two-ring or lower cyclic structure relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (Y) is preferably 50 parts by weight to 99 parts by weight, more preferably 70 parts by weight to 99 parts by weight, even more preferably 80 parts by weight to 98 parts by weight, particularly preferably 90 parts by weight to 97 parts by weight, and most preferably 92 parts by weight to 96 parts by weight.

[0087] The oligomer (Y) may contain a carboxyl group-containing monomer as a monomer component. As the carboxyl group-containing monomer, for example, (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc., may be mentioned, as well as the carboxyl group-containing monomer that may constitute an acrylic polymer. In addition, the acid anhydrides of these carboxyl group-containing monomers (for example, acid anhydride group-containing monomers such as maleic anhydride and itanoic anhydride) may also be mentioned as the carboxyl group-containing monomer.

[0088] The content of the carboxyl group-containing monomer relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (Y) is preferably 1 to 10 parts by weight, preferably 2 to 9 parts by weight, more preferably 3 to 8 parts by weight, and particularly preferably 4 to 7 parts by weight.

[0089] The monomer composition used to obtain the oligomer (Y) may contain other monomers in addition to the acrylic monomer having a two or less ring cyclic structure. Such other monomers may be of only one type or of two or more types.

[0090] Examples of other monomers include (meth)acrylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and isodecyl (meth)acrylate. alkyl esters; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; vinyl ester monomers such as vinyl acetate and vinyl propionate; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylate monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; olefin monomers such as ethylene, propylene, isoprene and butadiene; and vinyl ether monomers such as vinyl ether.

[0091] Examples of other monomers include polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, and hexyl di(meth)acrylate.

[0092] Other monomers include nitrogen atom-containing monomers (for example, (meth)acrylate aminoalkyl monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; (N-substituted) amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hydroxy(meth)acrylamide; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; and isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate). However, such nitrogen atom-containing monomers can cause the adhesive to yellow under heating, so it is preferable not to use them when it is not necessary.

[0093] The oligomer (X) or the oligomer (Y) can be prepared by any suitable polymerization method as long as the effects of the present invention are not impaired. Examples of the polymerization method for the acrylic polymer include a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, and a polymerization method using ultraviolet light irradiation, and the solution polymerization method is preferred in terms of transparency, water resistance, cost, and the like.

[0094] As the polymerization initiator, chain transfer agent, and the like that can be used in the polymerization, any appropriate ones can be adopted within a range that does not impair the effects of the present invention.

[0095] The amount of the polymerization initiator used may be any appropriate amount as long as the effects of the present invention are not impaired. For example, the amount used is preferably 0.1% by weight to 15% by weight based on the total amount of the monomer components.

[0096] The amount of the chain transfer agent used may be any appropriate amount as long as the effects of the present invention are not impaired. The amount used is preferably, for example, 0.01% by weight to 15% by weight based on the total amount of the monomer components.

[0097] In the solution polymerization method, various common solvents can be used. Examples of such solvents include organic solvents such as esters such as ethyl acetate and n-butyl acetate, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as n-hexane and n-heptane, alicyclic hydrocarbons such as cyclohexane and methylcyclohexane, and ketones such as methyl ethyl ketone and methyl isobutyl ketone. The solvent may be one type only or two or more types.

[0098] The oligomers (X) and (Y) have a weight average molecular weight of preferably 3,000 to 6,000, more preferably 3,300 to 5,500, and further preferably 3,500 to 5,000.

[0099] The weight average molecular weight of the oligomers (X) and (Y) can be controlled by the types and amounts of polymerization initiator and chain transfer agent, the temperature and time during polymerization, as well as the monomer concentration and monomer dropping rate.

[0100] When the pressure-sensitive adhesive composition a2 contains an acrylic polymer and an oligomer, the ratio of the acrylic polymer to the oligomer is preferably 10 to 35 parts by weight, more preferably 15 to 30 parts by weight, per 100 parts by weight of the acrylic polymer. When the pressure-sensitive adhesive composition a2 contains an acrylic polymer and an oligomer, the effects of the present invention can be more effectively achieved if the ratio of the acrylic polymer to the oligomer is within the above range.

[0101] The adhesive composition a2 may contain known additives, such as ultraviolet absorbers, antioxidants, light stabilizers, antiaging agents, tackifiers, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), surfactants, and antistatic agents, as necessary.

[0102] <1-3. Release sheet> A release sheet may be provided on the surface of the pressure-sensitive adhesive layer A2 for protection purposes. The release sheet may be one layer or two or more layers.

[0103] The thickness of the release sheet is preferably 5 μm to 300 μm, more preferably 10 μm to 200 μm, even more preferably 10 μm to 150 μm, particularly preferably 10 μm to 130 μm, and most preferably 20 μm to 120 μm, in order to better exhibit the effects of the present invention.

[0104] The release sheet includes a resin substrate film.

[0105] Examples of the resin substrate film include plastic films made of polyester-based resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); plastic films made of olefin-based resins containing α-olefin as a monomer component, such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); plastic films made of polyvinyl chloride (PVC); plastic films made of vinyl acetate-based resins; plastic films made of polycarbonate (PC); and plastic films made of polyphenylene sulfide (PPS). plastic films made of amide-based resins such as polyamide (nylon) and wholly aromatic polyamide (aramid); plastic films made of polyimide-based resins; plastic films made of polyether ether ketone (PEEK); plastic films made of olefin-based resins such as polyethylene (PE) and polypropylene (PP); plastic films made of fluorine-based resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer; and the like.

[0106] The resin substrate film may be a single layer film or may be two or more layers. The resin substrate film may be a stretched film.

[0107] The resin substrate film may be subjected to a surface treatment, such as a corona treatment, a plasma treatment, a chromic acid treatment, an ozone exposure, a flame exposure, a high-voltage shock exposure, an ionizing radiation treatment, or a coating treatment with a primer.

[0108] The resin substrate film may contain any appropriate additive within the range not impairing the effects of the present invention.

[0109] The release sheet may have a release layer to improve the releasability from the pressure-sensitive adhesive layer A2. When the release sheet has a release layer, the release layer side is directly laminated to the pressure-sensitive adhesive layer A2.

[0110] The material for forming the release layer may be any suitable material within the scope of the present invention. Examples of such materials include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and fatty acid amide-based release agents. Among these, silicone-based release agents are preferred. The release layer may be formed as a coating layer.

[0111] The thickness of the release layer may be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. Such a thickness is preferably 10 nm to 2000 nm, more preferably 10 nm to 1500 nm, further preferably 10 nm to 1000 nm, and particularly preferably 10 nm to 500 nm.

[0112] The release layer may be a single layer or may be two or more layers.

[0113] Examples of the silicone-based release layer include addition reaction type silicone resins. Specific examples of the addition reaction type silicone resins include KS-774, KS-775, KS-778, KS-779H, KS-847H, and KS-847T manufactured by Shin-Etsu Chemical Co., Ltd.; TPR-6700, TPR-6710, and TPR-6721 manufactured by Toshiba Silicone; and SD7220 and SD7226 manufactured by Toray Dow Corning. The coating amount (after drying) of the silicone-based release layer is preferably 0.01 g / m 2 ~2g / m 2 and more preferably 0.01 g / m 2 ~1g / m 2 and more preferably 0.01 g / m 2 ~0.5g / m 2 It is.

[0114] The release layer can be formed, for example, by applying the above-mentioned forming material onto any appropriate layer by a conventionally known application method such as reverse gravure coating, bar coating, or die coating, and then curing the applied material by heat treatment at about 120 to 200° C. If necessary, the heat treatment may be combined with irradiation with active energy rays such as ultraviolet rays.

[0115] The release sheet may have an antistatic layer.

[0116] The thickness of the antistatic layer may be any appropriate thickness within the range that does not impair the effects of the present invention. Such a thickness is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm, further preferably 7.5 nm to 800 nm, and particularly preferably 10 nm to 700 nm.

[0117] The antistatic layer may be a single layer or may be two or more layers.

[0118] As the antistatic layer, any suitable antistatic layer can be adopted as long as it can exhibit an antistatic effect, without impairing the effects of the present invention. Such an antistatic layer is preferably an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on any suitable substrate layer. Specifically, for example, an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on a resin substrate film. Specific coating methods include roll coating, bar coating, and gravure coating.

[0119] As the conductive polymer, any suitable conductive polymer may be adopted as long as the effect of the present invention is not impaired. Examples of such conductive polymers include conductive polymers in which a π-conjugated conductive polymer is doped with a polyanion. Examples of the π-conjugated conductive polymer include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of the polyanion include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, and polymethacrylic carboxylic acid. The conductive polymer may be one type only, or two or more types.

[0120] <1-4. Functional layer A3>

[0121] The reinforcing film may include a functional layer A3, a base layer A1, and a pressure-sensitive adhesive layer A2 in this order. That is, another embodiment of the reinforcing film is composed of a functional layer A3 (30), a base layer A1 (10), and a pressure-sensitive adhesive layer A2 (20) as shown in FIG.

[0122] The functional layer A3 is an optional layer that can impart various functions to the reinforcing film.

[0123] The thickness of the functional layer A3 may be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. Such a thickness is preferably 1 nm to 1000 nm, more preferably 2 nm to 800 nm, further preferably 5 nm to 400 nm, and particularly preferably 10 nm to 200 nm.

[0124] The functional layer A3 may be a single layer or may be two or more layers.

[0125] Any suitable functional layer may be used as the functional layer A3 as long as it does not impair the effects of the present invention. Examples of such functional layers include an antistatic layer, an antireflection layer, an antiglare layer, and a hard coat layer, and an antireflection layer may be selected in terms of being able to more effectively exhibit the effects of the present invention.

[0126] As the antireflection layer, any appropriate antireflection layer can be adopted as long as it does not impair the effects of the present invention. Examples of such antireflection layers include the antireflection layers described in JP-A-2019-144577 and the like.

[0127] As the functional layer A3, an antistatic layer may be preferably selected in order to exhibit an antistatic effect.

[0128] When both an antireflection layer and an antistatic layer are selected as the functional layer A3, it is preferable to dispose the antistatic layer on the base layer A1 side in order to better exhibit the function of the antireflection layer.

[0129] As the antistatic layer, any suitable antistatic layer may be used as long as it has an antistatic effect and does not impair the effects of the present invention. Such an antistatic layer is preferably an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on any suitable substrate layer. Specifically, for example, an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer on a substrate layer A1. Specific coating methods include roll coating, bar coating, and gravure coating.

[0130] As the conductive polymer, any suitable conductive polymer may be adopted as long as the effect of the present invention is not impaired. Examples of such conductive polymers include conductive polymers in which a π-conjugated conductive polymer is doped with a polyanion. Examples of the π-conjugated conductive polymer include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of the polyanion include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, and polymethacrylic carboxylic acid.

[0131] <1-5. Uses of reinforcing films, optical components with reinforcing films, electronic components with reinforcing films> The reinforcing film of the present invention is attached to an adherend which is any suitable member. Typically, the reinforcing film of the present invention is attached to an adherend which is an optical member or an electronic member. In this case, the exposed surface side of the pressure-sensitive adhesive layer A2 of the reinforcing film of the present invention is attached to an adherend which is an optical member or an electronic member. In this way, the optical member with the reinforcing film or the electronic member with the reinforcing film of the present invention is obtained. That is, the optical member with the reinforcing film or the electronic member with the reinforcing film of the present invention includes the reinforcing film of the present invention.

[0132] 2. Surface protection film The surface protective film is disposed on the base layer A1 side of the reinforcing film. When the base layer A1 has a functional layer A3, the surface protective film is disposed on the functional layer A3 side.

[0133] The thickness of the surface protection film may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 4 μm to 500 μm, more preferably 10 μm to 400 μm, further preferably 15 μm to 350 μm, and particularly preferably 20 μm to 300 μm.

[0134] The surface protective film includes a base material layer B1 and a pressure-sensitive adhesive layer B2. As long as the surface protective film includes the base material layer B1 and the pressure-sensitive adhesive layer B2, the surface protective film may include any other appropriate layers as long as the effects of the present invention are not impaired.

[0135] A release sheet may be provided on the surface of the pressure-sensitive adhesive layer B2 for protection.

[0136] A functional layer B3 may be provided on the surface of the base layer B1 in order to impart various functions.

[0137] The thickness of the surface protection film may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 5 μm to 500 μm, more preferably 10 μm to 450 μm, further preferably 15 μm to 400 μm, and particularly preferably 20 μm to 300 μm.

[0138] One embodiment of the surface protection film, as shown in FIG. 3, is composed of a base layer B1 (40), a pressure-sensitive adhesive layer B2 (50), and a release sheet (60).

[0139] One embodiment of the surface protection film, as shown in FIG. 4, comprises a functional layer B3 (70), a base layer B1 (40), an adhesive layer B2 (50), and a release sheet (60).

[0140] <2-1. Base material layer B1> As the base layer B1, a base material formed from any appropriate material may be used depending on the purpose, as long as the effect of the present invention is not impaired. Examples of such materials include those exemplified in the section <1-1. Base layer A1>.

[0141] The base material layer B1 may be a single layer or may be two or more layers.

[0142] The thickness of the base layer B1 may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 4 μm to 350 μm, more preferably 8 μm to 325 μm, further preferably 12 μm to 290 μm, and particularly preferably 15 μm to 205 μm.

[0143] The base layer B1 may contain an antistatic agent. For example, a resin sheet in which an antistatic agent is kneaded may be used as the base layer B1 containing an antistatic agent. Such a resin sheet may be formed from a base layer B1 forming composition containing a resin and an antistatic agent.

[0144] The base layer B1 itself may act as an antistatic agent. For example, when a metal foil is used as the material of the base layer B1, the base layer B1 itself may act as an antistatic agent.

[0145] The substrate layer B1 may be subjected to a surface treatment, such as a corona treatment, a plasma treatment, a chromic acid treatment, an ozone exposure, a flame exposure, a high-voltage shock exposure, an ionizing radiation treatment, or a coating treatment with a primer.

[0146] Examples of the organic coating material include those exemplified in <1-1. Base material layer A1>.

[0147] The substrate layer B1 may contain any other appropriate additives depending on the purpose, as long as the effects of the present invention are not impaired.

[0148] <2-2. Adhesive layer B2> The thickness of the pressure-sensitive adhesive layer B2 may be any appropriate thickness depending on the purpose, as long as the effects of the present invention are not impaired. Such a thickness is preferably 1 μm to 150 μm, more preferably 2 μm to 125 μm, even more preferably 3 μm to 110 μm, and particularly preferably 5 μm to 95 μm.

[0149] The adhesive layer B2 may be any adhesive layer made of an appropriate adhesive, provided that the effects of the present invention are not impaired. Examples of such adhesives include those constituting the adhesive layer described in JP 2019-127526 A, and preferably at least one selected from the group consisting of acrylic adhesives, urethane adhesives, and silicone adhesives described in the publication.

[0150] <2-3. Release sheet> A release sheet may be provided on the surface of the pressure-sensitive adhesive layer B2 for protection. The release sheet may be one layer or two or more layers.

[0151] For the release sheet that the surface protective film may have, the explanation in the section <1-3. Release sheet> may be cited.

[0152] <2-4. Functional layer B3>

[0153] The surface protective film may include a functional layer B3, a base layer B1, and a pressure-sensitive adhesive layer B2 in this order.

[0154] The functional layer B3 is a layer that may be provided optionally and is a layer that can impart various functions to the reinforcing film.

[0155] The thickness of the functional layer B3 may be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. Such a thickness is preferably 1 nm to 1000 nm, more preferably 2 nm to 800 nm, further preferably 5 nm to 400 nm, and particularly preferably 10 nm to 200 nm.

[0156] The functional layer B3 may be a single layer or may be two or more layers.

[0157] For the functional layer B3, the explanation in the section <1-4. Functional layer A3> may be cited.

[0158] ≪3. Reinforcement film with surface protection film≫ The reinforcing film with a surface protective film of the present invention has a surface protective film on the base layer A1 side of the reinforcing film of the present invention. When the reinforcing film of the present invention further has a functional layer A3 on the base layer A1, the surface protective film is provided on the surface of the functional layer A3.

[0159] The reinforcing film with a surface protective film of the present invention has a reinforcing film and a surface protective film. The reinforcing film with a surface protective film of the present invention may have any appropriate other layer as long as it has a reinforcing film and a surface protective film, as long as the effects of the present invention are not impaired.

[0160] In the reinforcing film with surface protective film of the present invention, the reinforcing film includes a base material layer A1 and a pressure-sensitive adhesive layer A2, and the surface protective film includes a base material layer B1 and a pressure-sensitive adhesive layer B2.

[0161] The thickness of the reinforcing film with surface protective film of the present invention may be any appropriate thickness depending on the purpose, as long as the effect of the present invention is not impaired. Such a thickness is preferably 9 μm to 1300 μm, more preferably 20 μm to 1050 μm, further preferably 35 μm to 900 μm, and particularly preferably 45 μm to 750 μm.

[0162] The reinforcing film with surface protective film of the present invention can be obtained by bonding the reinforcing film and the surface protective film together so that the base layer A1 (if a functional layer A3 is further provided on the base layer A1, then the functional layer A3) and the adhesive layer B2 of the surface protective film (if a release sheet is provided on the adhesive layer B2, then the adhesive layer B2 exposed by peeling off the release sheet) are directly laminated together.

[0163] One embodiment of the reinforcing film with surface protective film of the present invention is a form in which a reinforcing film consisting of a base material layer A1 (10) and an adhesive layer A2 (20) and a surface protective film consisting of a base material layer B1 (40) and an adhesive layer B2 (50) are bonded together so that the base material layer A1 (10) and the adhesive layer B2 (50) are directly laminated to each other, as shown in Figure 5.

[0164] ≪4. Usage of reinforcing film≫ The reinforcing film of the present invention is typically attached to an adherend that is an optical member or an electronic member. Specifically, the exposed surface of the pressure-sensitive adhesive layer A2 of the reinforcing film of the present invention is attached to an adherend that is an optical member or an electronic member. When a release sheet is provided on the surface of the pressure-sensitive adhesive layer A2, the release sheet is peeled off and the exposed pressure-sensitive adhesive layer A2 is attached to an adherend that is an optical member or an electronic member.

[0165] Examples of the adherend that is an optical or electronic member include LED, micro LED, mini LED, and OLED. A typical example of such an adherend is OLED.

[0166] In order to make better use of the effects exerted by the reinforcing film of the present invention, the OLED is preferably at least one selected from the group consisting of a foldable member, a flexible member, and a rollable member.

[0167] A foldable member is a member that has a movable bend (that can be folded), a flexible member is a member that can be bent, and a rollable member is a member that can be rolled up.

[0168] 5. How to use the reinforcing film with surface protection film The method of using the laminated film with surface protective film of the present invention is to expose the pressure-sensitive adhesive layer A2 of the reinforcing film with surface protective film of the present invention, attach the pressure-sensitive adhesive layer A2 to an adherend, and then peel off the surface protective film. In the reinforcing film with surface protective film of the present invention, when a release sheet is provided on the surface of the pressure-sensitive adhesive layer A2, first, peel off the release sheet to expose one of the pressure-sensitive adhesive layer surfaces of the pressure-sensitive adhesive layer A2, and attach the pressure-sensitive adhesive layer surface to an adherend. Then, peel off the surface protective film.

[0169] In this manner, a member is obtained in which the reinforcing film is attached to the adherend. EXAMPLES

[0170] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.

[0171] <Measurement of weight average molecular weight> The weight average molecular weight was measured by gel permeation chromatography (GPC). Specifically, the GPC measurement device was a product name "HLC-8120GPC" (manufactured by Tosoh Corporation) under the following conditions, and the weight average molecular weight was calculated based on the standard polystyrene equivalent value. (Molecular weight measurement conditions) Sample concentration: 0.2% by weight (tetrahydrofuran solution) Sample injection volume: 10μL Column: Product name "TSKguardcolumn SuperHZ-H (1 piece) + TSKgel SuperHZM-H (2 pieces)" (manufactured by Tosoh Corporation) Reference column: Product name "TSKgel SuperH-RC (1 piece)" (manufactured by Tosoh Corporation) Eluent: Tetrahydrofuran (THF) ·Flow rate: 0.6mL / min Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40℃

[0172] <Absolute value of the rate of change of in-plane retardation at a wavelength of 590 nm> The release sheet was peeled off from the reinforcing film obtained in the examples or comparative examples, and the in-plane retardation R0 from the substrate side was measured at a measurement wavelength of 590 nm using a polarization / retardation measurement system (Axometrics, "AxoScan"), which was defined as the in-plane retardation R01 (nm). Next, the reinforcing film obtained in the examples or comparative examples was stored in an environment of 60°C and 90% RH for one week, and then left at 23°C for 30 minutes to return to room temperature, and the release sheet was peeled off, and the in-plane retardation R0 from the substrate side was similarly measured for the remaining reinforcing film, which was defined as the in-plane retardation R02 (nm). Using the obtained values ​​of the in-plane retardation R01 (nm) and the in-plane retardation R02 (nm), the absolute value of the rate of change of the in-plane retardation (R0) at a wavelength of 590 nm, ΔR0 (nm) = |(R02-R01) / (R01) × 100|, was calculated.

[0173] <Haze change rate> The release sheet was peeled off from the reinforcing film obtained in the examples or comparative examples, and the haze was measured with a haze meter (manufactured by Murakami Color Co., Ltd., model: HM-150) to obtain the haze H1 (%). Next, the reinforcing film obtained in the examples or comparative examples was stored in an environment of 60°C and 90% RH for one week, and then left at 23°C for 30 minutes to return to room temperature, and the release sheet was peeled off, and the haze of the remaining reinforcing film was measured in the same manner to obtain the haze H2 (%). Using the obtained haze value, the haze change rate ΔH (%) = (H2-H1) / (H1) x 100 was calculated.

[0174] <Total light transmittance> The release sheet was peeled off from the reinforcing film obtained in each of the Examples and Comparative Examples, and the transmittance at 580 nm was measured using a spectrophotometer (manufactured by Hitachi, Ltd., model: U-4100).

[0175] <Adhesion to PET film> The reinforcing film (25 mm wide x 140 mm long) from which the release sheet had been removed was attached to a glass-backed PET film "Lumirror S10#25" (manufactured by Toray Industries, Inc.) using a 2 kg hand roller back and forth once. It was then left to stand for 30 minutes in an environmental temperature of 23°C. The evaluation sample obtained as described above was measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. After the evaluation sample was set in the tensile tester, the tensile test was started. The conditions of the tensile test were peel angle: 180 degrees, peel speed (pulling speed): 300mm / min. The load when the reinforcing film was peeled from the PET film was measured, and the average load at that time was taken as the adhesive strength of the reinforcing film to the PET film.

[0176] <Adhesive strength to PET film (after heating at 60℃ for 60 minutes)> The reinforcing film (25 mm wide x 140 mm long) from which the release sheet had been removed was attached to a glass-backed PET film "Lumirror S10#25" (manufactured by Toray Industries, Inc.) using a 2 kg hand roller in one pass and left in an environment at 60°C for 60 minutes. The evaluation sample obtained as described above was measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. After the evaluation sample was set in the tensile tester, the tensile test was started. The conditions of the tensile test were peel angle: 180 degrees, peel speed (pulling speed): 300mm / min. The load when the reinforcing film was peeled from the PET film was measured, and the average load at that time was taken as the adhesive strength of the reinforcing film to the PET film.

[0177] <Rainbow unevenness> The release sheet was peeled off from the reinforcing film obtained in the Example or Comparative Example, and the polarizing plate was laminated so that the transmission axis direction of the polarizing plate was parallel to the MD direction of the film substrate. Another polarizing plate was placed on the reinforcing film so that it was in a cross-Nicol configuration with the polarizing plate laminated to the reinforcing film. Fluorescent light was irradiated from below one of the polarizing plates, and the presence or absence of rainbow unevenness was evaluated by visual inspection of the transmitted light. Those that did not have rainbow unevenness were rated as OK, and those that did have rainbow unevenness were rated as NG.

[0178] [Production Example 1]: Production of (meth)acrylic polymer (1) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler, 65 parts of 2-ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 15 parts of N-vinylpyrrolidone (manufactured by Nippon Shokubai Co., Ltd.), 13 parts of hydroxyethyl acrylate (manufactured by Toa Gosei Co., Ltd.), 7 parts of methyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 63°C, and a polymerization reaction was carried out for 10 hours to prepare a solution of (meth)acrylic polymer (1) having a weight average molecular weight of 700,000 (solid concentration = 40% by weight).

[0179] [Production Example 2]: Production of (meth)acrylic polymer (2) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler, 100 parts of butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 7.5 parts of acrylic acid (manufactured by Toa Gosei Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 63°C and a polymerization reaction was carried out for 10 hours to prepare a solution of (meth)acrylic polymer (2) having a weight average molecular weight of 700,000 (solid concentration = 40% by weight).

[0180] [Production Example 3]: Production of (meth)acrylic polymer (3) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler, 96 parts of 2-ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 4 parts of hydroxyethyl acrylate (manufactured by Toa Gosei Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 63°C and a polymerization reaction was carried out for 10 hours to prepare a solution (solid concentration = 40% by weight) of a (meth)acrylic polymer (3) having a weight average molecular weight of 500,000.

[0181] [Production Example 4]: Production of (meth)acrylic oligomer (4) Cyclohexyl methacrylate as a monomer component [glass transition temperature of homopolymer (cyclohexyl methacrylate): 66 ° C]: 95 parts by weight, acrylic acid: 5 parts by weight, 2-mercaptoethanol as a chain transfer agent: 3 parts by weight, 2,2'-azobisisobutyronitrile as a polymerization initiator: 0.2 parts by weight, and toluene as a polymerization solvent: 103.2 parts by weight were charged into a separable flask and stirred for 1 hour while introducing nitrogen gas. In this way, oxygen in the polymerization system was removed, and then the temperature was raised to 70 ° C, reacted for 3 hours, and further reacted at 75 ° C for 2 hours to prepare a solution of (meth)acrylic oligomer (4) with a weight average molecular weight of 4000 (solid concentration = 50 wt%).

[0182] [Production Example 5]: Production of (meth)acrylic oligomer (5) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, a condenser, and a dropping funnel, 100 parts by weight of toluene, 60 parts by weight of dicyclopentanyl methacrylate (DCPMA) (product name: FA-513M, Hitachi Chemical Co., Ltd.), 40 parts by weight of methyl methacrylate (MMA), and 3.5 parts by weight of methyl thioglycolate as a chain transfer agent were added. Then, after stirring for 1 hour under a nitrogen atmosphere at 70°C, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added, and the mixture was reacted at 70°C for 2 hours, then at 80°C for 4 hours, and then at 90°C for 1 hour to prepare a solution of (meth)acrylic oligomer (5) having a weight average molecular weight of 4000 (solid content concentration = 51% by weight).

[0183] [Production Example 6]: Production of (meth)acrylic oligomer (6) Into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, a condenser, and a dropping funnel, 100 parts by weight of toluene, 40 parts by weight of methyl methacrylate (MMA), 20 parts by weight of butyl methacrylate (BMA), 20 parts by weight of 2-ethylhexyl methacrylate (2-EHMA), 17 parts by weight of a polyorganosiloxane skeleton-containing methacrylate monomer having a functional group equivalent of 900 g / mol (trade name: X-22-174ASX, manufactured by Shin-Etsu Chemical Co., Ltd.), 3 parts by weight of a polyorganosiloxane skeleton-containing methacrylate monomer having a functional group equivalent of 4600 g / mol (trade name: X-22-174DX, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.51 parts by weight of methyl thioglycolate as a chain transfer agent were added. Then, after stirring at 70°C under a nitrogen atmosphere for 1 hour, 0.2 parts by weight of azobisisobutyronitrile was added as a thermal polymerization initiator and reacted at 70°C for 2 hours, after which 0.1 parts by weight of azobisisobutyronitrile was added as a thermal polymerization initiator and subsequently reacted at 80°C for 5 hours to prepare a solution of (meth)acrylic oligomer (6) having a weight average molecular weight of 21,300 (solid content concentration = 50% by weight).

[0184] [Production Example 7]: Production of (meth)acrylic pressure-sensitive adhesive composition (1) To the solution of (meth)acrylic polymer (1) obtained in Production Example 1, 1.0 part by weight of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) was added as a crosslinking agent in terms of solid content per 100 parts by weight of the solid content of the solution of (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate to a total solid content of 25% by weight, followed by stirring with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (1).

[0185] [Production Example 8]: Production of (meth)acrylic pressure-sensitive adhesive composition (2) To the solution of the (meth)acrylic polymer (2) obtained in Production Example 2, 0.075 parts by weight, calculated as solids, of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent and 20 parts by weight, calculated as solids, of the solution of the (meth)acrylic oligomer (4) obtained in Production Example 4 were added relative to 100 parts by weight of the solids of the solution of the (meth)acrylic polymer (2), and the solution was diluted with ethyl acetate so that the solids content of the entire solution became 25% by weight. The solution was stirred with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (2).

[0186] [Production Example 9]: Production of (meth)acrylic pressure-sensitive adhesive composition (3) To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight, calculated as solids, of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent and 5 parts by weight, calculated as solids, of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5 were added relative to 100 parts by weight of the solids of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate to a total solids content of 25% by weight. The mixture was stirred with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (3).

[0187] [Production Example 10]: Production of (meth)acrylic pressure-sensitive adhesive composition (4) To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight, calculated as solids, of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent and 7.5 parts by weight, calculated as solids, of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5 were added relative to 100 parts by weight of the solids of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate to a total solids content of 25% by weight. The mixture was stirred with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (4).

[0188] [Production Example 11]: Production of (meth)acrylic pressure-sensitive adhesive composition (5) To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight, calculated as solids, of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent and 10 parts by weight, calculated as solids, of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5 were added relative to 100 parts by weight of the solids of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate so that the total solids content was 25% by weight. The mixture was stirred with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (5).

[0189] [Production Example 12]: Production of (meth)acrylic pressure-sensitive adhesive composition (6) To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 4.0 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) was added as a crosslinking agent in terms of solid content per 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate to a total solid content of 25% by weight. The mixture was stirred with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (6).

[0190] [Production Example 13]: Production of (meth)acrylic pressure-sensitive adhesive composition (7) To the solution of the (meth)acrylic polymer (1) obtained in Production Example 1, 1.0 part by weight, calculated as solid content, of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent and 2.0 parts by weight, calculated as solid content, of the solution of the (meth)acrylic oligomer (6) obtained in Production Example 6 were added relative to 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate to a total solid content of 25% by weight, followed by stirring with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (7).

[0191] [Production Example 14]: Production of (meth)acrylic pressure-sensitive adhesive composition (8) To the solution of the (meth)acrylic polymer (1) obtained in Production Example 1, 2.5 parts by weight, calculated as solids, of Coronate HL (manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent and 2.5 parts by weight, calculated as solids, of the solution of the (meth)acrylic oligomer (6) obtained in Production Example 6 were added relative to 100 parts by weight of the solids of the solution of the (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate to a total solids content of 25% by weight, followed by stirring with a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (8).

[0192] [Production Example 15]: Production of coating composition for forming anti-reflection layer In a 200 mL glass container, 60 g of ethanol, 30 g of an aqueous dispersion sol of ZnO fine particles (average primary particle diameter: 20 nm, average aggregate particle diameter: 40 nm, solid content equivalent concentration: 20 wt%), and 10 g of tetraethoxysilane (SiO2 solid content concentration: 29 wt%) were placed, and an aqueous ammonia solution was added to adjust the pH to 10. The mixture was stirred at 20°C for 6 hours to obtain 100 g of a dispersion liquid of core-shell particles (solid content concentration: 6 wt%). 100 g of a strongly acidic cation exchange resin (total exchange capacity: 2.0 meq / mL or more) was added to the obtained dispersion liquid of core-shell particles, and the mixture was stirred for 1 hour to adjust the pH to 4. The strongly acidic cation exchange resin was removed by filtration, and a dispersion liquid of spherical hollow fine particles made of SiO2 was obtained. The obtained dispersion liquid was concentrated to a solid content concentration of 20 wt% by ultrafiltration. The spherical hollow fine particles were secondary aggregated. The thickness of the shell of the hollow spherical particles was 5 nm, which was 1 / 6 of the average primary particle size. The average aggregate particle size of the hollow spherical particles was 40 nm, and the aspect ratio was 1.0. A 200 mL glass container was charged with 2 g of the obtained dispersion liquid of spherical hollow microparticles (solid concentration: 20 wt%), 2 g of a dispersion liquid of fibrous solid microparticles (Nissan Chemical Industries, Ltd., IPA-ST-UP, average agglomerated particle size (average primary particle size): 90 nm, aspect ratio: 7.0, solid concentration: 15 wt%), 90 g of ethanol, and 6 g of a silicic acid oligomer solution (solid concentration: 5 wt%), and the mixture was stirred for 10 minutes to obtain a coating composition for forming an antireflection layer.

[0193] [Production Example 16]: Production of TAC film substrate (A) having an anti-reflection layer The coating composition for forming an antireflection layer obtained in Production Example 15 was applied to one side of a cellulose triacetate (hereinafter sometimes referred to as "TAC") film (TG60UL, manufactured by Fujifilm Corporation), spin-coated at a rotation speed of 200 rpm for 60 seconds to make the coating uniform, and then dried at 200°C for 30 minutes to form an antireflection layer with a thickness of 100 nm. In this manner, a cellulose triacetate film substrate having an antireflection layer was obtained.

[0194] [Production Example 17]: Production of PET film substrate (B) having an anti-reflection layer The coating composition for forming an antireflection layer obtained in Production Example 15 was applied to one side of a polyethylene terephthalate (hereinafter sometimes referred to as "PET") film (Lumirror U48, manufactured by Toray Industries, Inc.), spin-coated at a rotation speed of 200 rpm for 60 seconds to make it uniform, and then dried at 200°C for 30 minutes to form an antireflection layer with a thickness of 100 nm. In this way, a polyethylene terephthalate film substrate having an antireflection layer was obtained.

[0195] [Production Example 18]: Production of Surface Protection Film (C) The (meth)acrylic adhesive composition (7) obtained in Production Example 13 was applied to a substrate made of polyester resin (trade name: "Lumirror S10", thickness 38 μm, manufactured by Toray Industries, Inc.) with a fountain roll so that the thickness after drying was 21 μm, and the substrate was cured and dried under conditions of a drying temperature of 130° C. and a drying time of 30 seconds. In this manner, an adhesive layer was produced on the substrate. Next, the silicone-treated surface of a release sheet made of polyester resin having a thickness of 25 μm and one side of which was silicone-treated (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) was bonded to the surface of the obtained adhesive layer to obtain a surface protection film (C). The obtained surface protection film (C) was aged at room temperature for 7 days.

[0196] Example 1 The (meth)acrylic adhesive composition (1) was applied to the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of a polyester resin having a thickness of 25 μm and one side of which was silicone-treated, so that the thickness after drying would be 25 μm, and the sheet was cured and dried under conditions of a drying temperature of 130° C. and a drying time of 3 minutes. In this way, an adhesive layer formed from the (meth)acrylic adhesive composition (1) was provided on the silicone-treated surface. Next, the surface of the obtained adhesive layer was bonded to the surface of the TAC film substrate (A) having an anti-reflection layer on which the anti-reflection layer was not applied, to obtain a reinforcing film (1). The obtained reinforcing film (1) was aged at room temperature for 7 days. The results are shown in Table 1.

[0197] Example 2 A reinforcing film (2) was obtained in the same manner as in Example 1, except that the substrate was changed to a TAC film (TG60UL, manufactured by Fujifilm Corporation) as shown in Table 1. The results are shown in Table 1.

[0198] Example 3 As shown in Table 1, the same procedure as in Example 1 was carried out except that the substrate was changed to a polyimide (hereinafter sometimes referred to as "PI") film (Neoprim S-100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), to obtain a reinforcing film (3). The results are shown in Table 1.

[0199] Example 4 A reinforcing film (4) was obtained in the same manner as in Example 1, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (2) as shown in Table 1. The results are shown in Table 1.

[0200] Example 5 A reinforcing film (5) was obtained in the same manner as in Example 2, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (2) as shown in Table 1. The results are shown in Table 1.

[0201] Example 6 A reinforcing film (6) was obtained in the same manner as in Example 1, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (7) as shown in Table 1. The results are shown in Table 1.

[0202] Example 7 A reinforcing film (7) was obtained in the same manner as in Example 2, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (7) as shown in Table 1. The results are shown in Table 1.

[0203] Example 8 A reinforcing film (8) was obtained in the same manner as in Example 3, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (7) as shown in Table 1. The results are shown in Table 1.

[0204] Example 9 A reinforcing film (9) was obtained in the same manner as in Example 1, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (8) as shown in Table 1. The results are shown in Table 1.

[0205] Example 10 A reinforcing film (10) was obtained in the same manner as in Example 2, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (8) as shown in Table 1. The results are shown in Table 1.

[0206] Example 11 A reinforcing film (11) was obtained in the same manner as in Example 3, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (8) as shown in Table 1. The results are shown in Table 1.

[0207] [Table 1]

[0208] Example 12 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (1) obtained in Example 1 to obtain a reinforcing film (12) with a surface protective film.

[0209] Example 13 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (2) obtained in Example 2 to obtain a reinforcing film (13) with a surface protective film.

[0210] Example 14 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (3) obtained in Example 3 to obtain a reinforcing film (14) with a surface protective film.

[0211] Example 15 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (4) obtained in Example 4 to obtain a reinforcing film (15) with a surface protective film.

[0212] Example 16 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (5) obtained in Example 5 to obtain a reinforcing film (16) with a surface protective film.

[0213] Example 17 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (6) obtained in Example 6 to obtain a reinforcing film (17) with a surface protective film.

[0214] Example 18 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (7) obtained in Example 7 to obtain a reinforcing film (18) with a surface protective film.

[0215] Example 19 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (8) obtained in Example 8 to obtain a reinforcing film (19) with a surface protective film.

[0216] Example 20 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (9) obtained in Example 9 to obtain a reinforcing film (20) with a surface protective film.

[0217] Example 21 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (10) obtained in Example 10 to obtain a reinforcing film (21) with a surface protective film.

[0218] Example 22 The surface protective film (C) obtained in Production Example 18 was attached to the substrate of the reinforcing film (11) obtained in Example 11 to obtain a reinforcing film (22) with a surface protective film.

[0219] Comparative Example 1 The (meth)acrylic adhesive composition (3) was applied to the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of a polyester resin having a thickness of 25 μm and one side of which was silicone-treated, so that the thickness after drying was 25 μm, and the sheet was cured and dried under conditions of a drying temperature of 130° C. and a drying time of 3 minutes. In this way, an adhesive layer formed from the (meth)acrylic adhesive composition (3) was provided on the silicone-treated surface. Next, the surface of the obtained adhesive layer was bonded to the surface of the TAC film substrate (A) having an anti-reflection layer on which the anti-reflection layer was not applied, to obtain a reinforcing film (C1). The obtained reinforcing film (C1) was aged at room temperature for 7 days. The results are shown in Table 2.

[0220] Comparative Example 2 A reinforcing film (C2) was obtained in the same manner as in Comparative Example 1, except that the substrate was changed to a TAC film (TG60UL, manufactured by Fujifilm Corporation) as shown in Table 2. The results are shown in Table 2.

[0221] Comparative Example 3 A reinforcing film (C3) was obtained in the same manner as in Comparative Example 1, except that the (meth)acrylic pressure-sensitive adhesive composition (3) was changed to the (meth)acrylic pressure-sensitive adhesive composition (4) as shown in Table 2. The results are shown in Table 2.

[0222] Comparative Example 4 A reinforcing film (C4) was obtained in the same manner as in Comparative Example 2, except that the (meth)acrylic pressure-sensitive adhesive composition (3) was changed to the (meth)acrylic pressure-sensitive adhesive composition (4) as shown in Table 2. The results are shown in Table 2.

[0223] Comparative Example 5 A reinforcing film (C5) was obtained in the same manner as in Comparative Example 1, except that the (meth)acrylic pressure-sensitive adhesive composition (3) was changed to the (meth)acrylic pressure-sensitive adhesive composition (5) as shown in Table 2. The results are shown in Table 2.

[0224] Comparative Example 6 A reinforcing film (C6) was obtained in the same manner as in Comparative Example 2, except that the (meth)acrylic pressure-sensitive adhesive composition (3) was changed to the (meth)acrylic pressure-sensitive adhesive composition (5) as shown in Table 2. The results are shown in Table 2.

[0225] Comparative Example 7 A reinforcing film (C7) was obtained in the same manner as in Example 1, except that the substrate was changed to a PET film substrate (B) having an antireflection layer as shown in Table 2. The results are shown in Table 2.

[0226] Comparative Example 8 A reinforcing film (C8) was obtained in the same manner as in Example 1, except that the substrate was changed to a PET film (Lumirror U48, manufactured by Toray Industries, Inc.) as shown in Table 2. The results are shown in Table 2.

[0227] Comparative Example 9 A reinforcing film (C9) was obtained in the same manner as in Comparative Example 7, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (2) as shown in Table 2. The results are shown in Table 1.

[0228] Comparative Example 10 A reinforcing film (C10) was obtained in the same manner as in Comparative Example 8, except that the (meth)acrylic pressure-sensitive adhesive composition (1) was changed to the (meth)acrylic pressure-sensitive adhesive composition (2) as shown in Table 2. The results are shown in Table 1.

[0229] [Table 2] [Industrial Applicability]

[0230] The reinforcing film and the reinforcing film with a surface protective film of the present invention can be used typically in the fields of optical members and electronic members. [Explanation of symbols]

[0231] 1000 Reinforcement film with surface protection film 100 Reinforcement film 200 Surface protection film 10 Base material layer A1 20 Adhesive layer A2 30 Functional layer A3 40 Base material layer B1 50 Adhesive layer B2 60 Release Sheet 70 Functional layer B3

Claims

1. A reinforcing film with a surface protective film, comprising a base material layer A1 and a pressure-sensitive adhesive layer A2, and a surface protective film on the base material layer A1 side of the reinforcing film, It is attached to an adherend which is an optical component, the base layer A1 is a resin sheet made of triacetyl cellulose or polyimide, the pressure-sensitive adhesive layer A2 is formed from a pressure-sensitive adhesive composition a2, The pressure-sensitive adhesive composition a2 includes an acrylic polymer and at least one selected from the group consisting of a polyfunctional isocyanate-based crosslinking agent and an epoxy-based crosslinking agent, the pressure-sensitive adhesive composition a2 does not contain an oligomer (X) having a weight average molecular weight of 3,000 to 6,000 obtained from a monomer composition containing 50% by weight or more of an acrylic monomer having a tricyclic or higher cyclic structure, The reinforcing film has an absolute value of a rate of change in an in-plane retardation (R0) at a wavelength of 590 nm after storage for one week in an environment of 60° C. and 90% RH of 20.0% or less. Reinforcing film with surface protection film.

2. The reinforcing film with a surface protective film according to claim 1 , wherein the reinforcing film has a haze change rate of 10.0% or less after being stored for one week in an environment of 60° C. and 90% RH.

3. The reinforcing film with a surface protective film according to claim 1 or 2, wherein the reinforcing film has a total light transmittance of 80% or more.

4. A reinforcing film with a surface protective film as described in any one of claims 1 to 3, wherein after the adhesive layer A2 is attached to a PET film and left at 23°C for 30 minutes, the adhesive strength to the PET film is 0.30 N / 25 mm or more at a peel angle of 180 degrees and a peel speed of 300 mm / min.

5. A method for using a reinforcing film with a surface protective film, comprising exposing the adhesive layer A2 provided on the reinforcing film with a surface protective film described in any one of claims 1 to 4, attaching the adhesive layer A2 to an adherend which is an optical component, and then peeling off the surface protective film.

Citation Information

Patent Citations

  • JP1988066199A

  • Thermosetting tacky adhesive sheet

    JP2001262101A

  • Adhesive composition and pressure sensitive adhesive sheet using the same

    JP2006022313A

  • Adhesive composition and adhesive sheet using this

    JP2008169307A

  • Optically compensatory plate, polarizing plate with optically compensatory layer using the same, method for producing the optically compensatory plate and liquid crystal display device using those

    JP2008282020A